Efficacy and brain modulation mechanisms of acupuncture for chronic prostatitis/chronic pelvic pain syndrome revealed by structural MRI changes - Wang, Zhen; Wu, Jinmei; Deng, Cong; Hu, Yongbo; Shi, Songshan; Liu, Shaowei; Huang, Xinfei; Chen, Jianhuai (Frontiers in Neurology, 2025)
IntroductionChronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) has been considered to be associated with abnormal brain function and structure. Acupuncture is a promising therapy for CP/CPPS, however, the underlying brain modulation mechanisms of acupuncture for CP/CPPS are still unclear.MethodsA total of 25 CP/CPPS patients and 25 matched-healthy controls (HCs) were enrolled. All patients received acupuncture treatment 3 times weekly for 4 weeks with a total of 12 sessions [acupoints including Guanyuan (RN4), Zhongji (RN3), Zusanli (LR10), Zuwuli (ST36), Sanyinjiao (SP6), and Yinlingquan (SP9)]. The efficacy was evaluated by the National Institute of Health-Chronic Prostatitis Symptom Index (NIH-CPSI). In addition, structural T1-weighted magnetic resonance imaging (MRI) brain scans were acquired from all patients before and after treatment, as well as HCs. MRI data were preprocessed and the measures of gray matter volume and density, as well as white matter volume and density, were calculated for all subjects. Finally, all these measures were compared between patients (before and after treatment) and HCs, and were also compared within patients before and after treatment. Moreover, the relationships between brain structure and NIH-CPSI scores were also evaluated.ResultsAfter treatment, CP/CPPS patients demonstrated decreased scores in the scale of NIH-CPSI and its subscales. Compared with HCs, both CP/CPPS patients before and after treatment showed increased gray matter volume and density, as well as increased white matter volume and density, especially in the frontal and parietal regions. After treatment, CP/CPPS patients showed decreased gray matter volume in the left middle cingulate gyrus, as well as increased gray matter volume and density in the left middle occipital gyrus. In addition, these structural brain abnormalities were related to NIH-CPSI scores of patients while the changes of NIH-CPSI scores were associated with the changes of structural changes in the brain of CP/CPPS patients before and after treatment.ConclusionThese findings suggested that the development of CP/CPPS might be associated with the increased gray matter and white matter in the frontal, cingulate and parietal regions. The effects of acupuncture in improving clinical symptoms of CP/CPPS might be achieved by reducing the gray matter volume in the left middle cingulate gyrus.